"Nothing about us without us:" The perspectives of autistic geoscientists on inclusive instructional practices in geoscience education. Issue 4 (1st October 2020) - Kingsbury, Cole G.; Sibert, Elizabeth C.; Killingback, Zachary; Atchison, Christopher L.
Abstract: Increasingly more students with disabilities, including autistic or otherwise neurodiverse students, are studying for degrees in STEM field subjects. In recent years, there has been an increased effort from the geoscience education community to make teaching more accessible and inclusive to these students. However, much of the literature on this topic lacks the voice of the individuals these practices aim to serve. This, combined with the medical, deficit-based understanding of autism typically presented in the literature, has resulted in the perpetuation of harmful stereotypes, along with recommendations that may not actually serve as best practice. Here we present a more accurate and holistic explanation of what autism actually is, using our lived experiences as autistic geoscientists. We then outline a comprehensive framework for best supporting autistic and neurodiverse geoscience students, with a focus on field-based learning. This framework includes three pillars: (a) develop effective communication pathways with autistic students, (b) presume competence and include autistic students in the planning of their own accommodations, and (c) employ strategies for expectation management. We also touch on the importance of recognizing the sensory processing aspects of autism spectrum conditions and suggest strategies for minimizing these difficulties in a field environment. By centering autistic voices in the discussion of how to support autistic geoscience students, we hope to change the narrative of inclusion for this diverse, but significant population.